Synthesis and Characterization of Cu(II)-EDTA Complexes: Antibacterial Studies (Escherichia coli, Staphylococcus aureus) and Inhibition of Dengue Virus Serotype 2 in Vero Cell - Kinetasari, Theresia Janice; Sucipto, Teguh Hari; Nugroho, Browi; Hariyono, Hariyono; Rehman, Saifur (Institute of Topical Disease Universitas Airlangga, 2025)
The Cu(II)-EDTA complex is known to have antibacterial and antiviral potential, but its effectiveness against pathogenic bacteria and dengue virus serotype 2 (DENV-2) still needs to be studied. This study synthesized and characterized the Cu(II)-EDTA complex of CuSO4 precursors, and then tested the antibacterial activity against Escherichia coli and Staphylococcus aureus, as well as the antiviral activity against DENV-2 in Vero cells. This study successfully synthesized and characterized the Cu(II)-EDTA complex using CuSO4 as a precursor through the solvothermal method, producing blue crystals with a Cu ratio of 1:1. DSC analysis showed thermal stability up to 250°C with an endothermal peak at 270-300°C. The particles are 6.31 nm in size with a PDI of 0.076, indicating uniform distribution with nanoparticle size (<100 nm). FTIR confirms the formation of the complex through significant shifts in the O-H and C=O bands. SEM shows a layered morphology that can affect the solubility and release of substances. UV-Vis shows maximum absorbance peaks of EDTA at 244 nm and CuSO4 at 740 nm. Antibacterial tests of Cu(II)-EDTA against E. coli and S. aureus showed that Cu(II)-EDTA had less activity than pure CuSO4. For DENV-2, CuSO4 was more effective with an EC50 value of 77.86 μg/mL, lower than Cu(II)-EDTA 356.13 μg/mL, indicating that CuSO4 was better at inhibiting viral replication.